Kajian Proses Penciptaan Karya Kolaboratif The Bayan Tale Seniman Erwin Windu Pranata Di Artjog Kids 2023 - Afandi, Nizar Mohamad; Sucitra, I Gede Arya; Witjaksono, Bambang (Journal of Contemporary Indonesian Art, 2025)
This study analyzes the creation process of the collaborative participatory artwork The Bayan Tale by artist Erwin Windu Pranata at ARTJOG KIDS 2023. The research aims to understand how the concept of collaborative art was implemented in a project involving children. Using a qualitative-descriptive method, data was collected through participant observation, in-depth interviews, and document analysis, framed by theories of participatory culture, relational, and dialogical aesthetics. The findings show that the project was a manifestation of ARTJOG's vision of inclusivity and Erwin's artistic practice. The creative process featured a dynamic spectrum of participation: children had high agency in the ideation and performative activation stages, while the artist maintained technical and curatorial control. The artist acted as a facilitator and "aesthetic translator," transforming children's imaginations into a coherent work. In conclusion, The Bayan Tale successfully created a democratic and empowering space for social interaction. The project transcended being a mere art object to become a relational event that blends local cultural values of gotong royong with global contemporary art discourse, proving a functional and effective collaborative model.Kajian ini menganalisis proses penciptaan karya partisipatoris kolaboratif The Bayan Tale oleh seniman Erwin Windu Pranata di ARTJOG KIDS 2023. Penelitian ini bertujuan untuk memahami bagaimana konsep seni kolaboratif diimplementasikan dalam sebuah proyek yang melibatkan anak-anak. Dengan metode kualitatif-deskriptif, data dikumpulkan melalui observasi partisipan, wawancara mendalam, dan analisis dokumen, serta dibingkai oleh teori budaya partisipatoris, estetika relasional, dan dialogis. Hasil penelitian menunjukkan bahwa proyek ini merupakan manifestasi dari visi inklusivitas ARTJOG dan praktik artistik Erwin. Proses kreatifnya menampilkan spektrum partisipasi dinamis: anak-anak memiliki agensi tinggi dalam tahap ideasi dan aktivasi performatif, sementara seniman memegang kendali teknis dan kuratorial. Seniman berperan sebagai fasilitator dan "penerjemah estetis" yang mewujudkan imajinasi anak-anak menjadi karya koheren. The Bayan Tale berhasil menciptakan ruang interaksi sosial yang demokratis dan memberdayakan. Proyek ini melampaui sekadar objek seni menjadi sebuah peristiwa relasional yang memadukan nilai budaya lokal gotong royong dengan wacana seni kontemporer global, membuktikan model kolaborasi yang fungsional dan efektif.